Meiotic Heterogeneity of Trivalent Structure and Interchromosomal Effect in Blastocysts With Robertsonian Translocations - Zhang, Shuo; Lei, Caixia; Wu, Junping; Zhou, Jing; Xiao, Min; Zhu, Saijuan; Xi, Yanping; Fu, Jing; Sun, Yijuan; Xu, Congjian; Sun, Xiaoxi (Frontiers in Genetics, 2021)
Background Robertsonian translocations are common structural rearrangements and confer an increased genetic reproductive risk due to the formation of trivalent structure during meiosis. Studies on trivalent structure show meiotic heterogeneity between different translocation carriers, although the factors causing heterogeneity have not been well elaborated in blastocysts. It is also not yet known whether interchromosomal effect (ICE) phenomenon occurs in comparison with suitable non-translocation control patients. Herein, we aimed to evaluate the factors that cause meiotic heterogeneity of trivalent structure and the ICE phenomenon. Methods We designed a retrospective study, comprising 217 Robertsonian translocation carriers and 134 patients with the risk of transmitting monogenic inherited disorders (RTMIDs) that underwent preimplantation genetic testing (PGT). Data was collected between March 2014 and December 2019. The segregation products of trivalent structure were analyzed based on the carrier’s gender, age and translocation type. In addition, to analyze ICE phenomenon, aneuploidy abnormalities of non-translocation chromosomes from Robertsonian translocation carriers were compared with those from patients with RTMIDs. Results We found that the percentage of male carriers with alternate segregation pattern was significantly higher [P < 0.001, odds ratio (OR) = 2.95] than that in female carriers, while the percentage of adjacent segregation pattern was lower (P < 0.001, OR = 0.33). By contrast, no difference was observed between young and older carriers when performing stratified analysis by age. Furthermore, segregation pattern was associated with the D;G chromosomes involved in Robertsonian translocation: the rate of alternate segregation pattern in Rob(13;14) carriers was significantly higher (P = 0.010, OR = 1.74) than that in Rob(14;21) carriers, whereas the rate of adjacent segregation pattern was lower (P = 0.032, OR = 0.63). Moreover, the results revealed that the trivalent structure could significantly increase the frequencies of chromosome aneuploidies 1.30 times in Robertsonian translocation carriers compared with patients with RTMIDs (P = 0.026), especially for the male and young subgroups (P = 0.030, OR = 1.35 and P = 0.012, OR = 1.40), while the mosaic aneuploidy abnormalities presented no statistical difference. Conclusions Our study demonstrated that meiotic segregation heterogeneity of trivalent structure is associated with the carrier’s gender and translocation type, and it is independent of carrier’s age. ICE phenomenon exists during meiosis and then increases the frequencies of additional chromosome abnormalities.